Echo burning - Child, Lee (London : BCA, 2001)
While hitchhiking through West Texas, former MP Jack Reacher encounters a young woman seeking protection for herself and her little girl from her monstrous husband, due to be released from jail, and his horrible family
"A Jack Reacher novel."
Keywords: Reacher, Jack (Fictitious character) -- Fiction; Private investigators -- Fiction; Private investigators -- Texas -- Fiction; Texas -- Fiction; Fiction; Suspense stories; Mystery fiction